Ultrasound Elastography for Characterization of Focal Liver Lesions - Dong, Yi; Koch, Jonas; Alhyari, Amjad; Safai Zadeh, Ehsan; Görg, Christian; Wang, Wen-Ping; Berzigotti, Annalisa; Dietrich, Christoph F. (Zeitschrift für Gastroenterologie, 2022)
Focal liver lesions (FLL) are typically detected by conventional ultrasound or other imaging modalities. After the detection of FLL, further characterization is essential, and this can be done by contrast-enhanced imaging techniques, e.g., contrast-enhanced ultrasound (CEUS) and magnetic resonance imaging (MRI) or by means of biopsy with histological evaluation. Elastographic techniques are nowadays integrated into high-end ultrasound systems and their value for the detection of severe liver fibrosis and cirrhosis has been shown in studies and meta-analyses. The use of an ultrasound elastographic technique for the differentiation of malignant and benign liver tumors is less well-established. This review summarizes the current data on utility and performance of ultrasound elastography for the characterization of FLL.
Keywords: Elastografie; fokale Leberläsionen; Lebertumoren; Steifheit; Ultraschall